PURIFICATION AND CHARACTERISATION OF IMMUNOGLOBULINS FROM THE SERUM OF A CATFISH, CLARIAS GARIEPINUS (BURCHELL, 1822) - Rathore, Gaurav; Swaminathan, T. Raja; Rashee, Shaista; Parvez, Najeeb; Mastan, S. A.; Qureshi, T . A. (Journal of Indian Fisheries Association, 2015)
Attempts have been made to characterize and purify immunoglobulinsfrom the serum of Clarias gariepinus, which has been immunized with bovineserum albumen. Initially, the proteins in the serum were chromatographedsuccessively by affinity chromatography column. The affinity-purified fractionwas concentrated and checked in SDS-PAGE, two bands of heavy chain andtwo bands of light chain were observed. Since teleost immunoglobulins havebeen shown to belong to a single class, the extra bands in light and heavychains in the present study might be the breakdown of immunoglobulin orsome unpurified contaminants. The affinity-purified fraction was alsosubjected to gel filtration chromatography column.Keywords: Clarias gariepinus, Immunoglobulin, Serum.